2012
DOI: 10.5505/tjtes.2012.09735
|View full text |Cite
|
Sign up to set email alerts
|

Management of Inhalation Injury and Respiratory Complications in Burns Intensive Care Unit

Abstract: AMAÇİnhalasyon yaralanması yüksek mortalite oranlarına sahiptir ve belirgin kalıcı pulmoner fonksiyon bozukluğu riski taşımaktadır. İnhalasyon yaralanması ve sonuçları, klinik yönetiminde ana rol oynayan solunum terapistlerine, hemşirelere ve doktorlara ciddi zorluklar oluşturur. Çalış-mamızda inhalasyon yaralanmalı hasta serimizdeki klinik tecrübelerimizi ve noninvazif mekanik ventilatör (NIMV) desteğinin rolünü bildirmeyi amaçladık. GEREÇ VE YÖNTEMAnkara Numune Eğitim ve Araştırma Hastanesi Yanık Yoğun Bakım… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Respiratory complications are one of the major determinants of mortality in burn patients, particularly if associated with inhalation injury. 1…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory complications are one of the major determinants of mortality in burn patients, particularly if associated with inhalation injury. 1…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that noninvasive ventilation can be used as initial ventilatory support in patients with SII provided that they are conscious and hemodynamically stable. ( 19 ) …”
Section: Airway Inhalation Injurymentioning
confidence: 99%